CHINESE WORKERS IN RUSSIA AS SIGNIFICANT FORCE IN MARXISM SPREAD - Baiying, Cao; Yanhong, Ning (Tambov University Review. Series: Humanities, 2016)
The urgent research topic of today is the question of life and activities of Chinese migrants in Russia in different historical periods. This problem field is extremely important for research, because migrants staying in the territory of another state always lead to close cooperation of people and civilizations, which has a direct impact on the further development of bilateral relations at various levels. In the first quarter of the XX century there was a rapid spread of Marxist ideas in China that took place primarily under the influence of the revolutionary processes in Russia. The significant force in the spread of the ideas of Marxism began to Chinese workers laboured in many regions of Russia. Their fate and life paths were different, but, in one or another way, almost all of them turned out to be closely linked to the Chinese revolution and the transformation process in the Chinese society of the middle of the XX century. The inevitability of the broad support Russian revolutionary ideas be the Chinese migrants is substantiated, the inevitability of the obvious choice of the Chinese workers the way of active participation in the revolutionary transformations in Russia and China is proved, the extent of their involvement in the spread of Marxism after their returning to China is analyzed.